Virtual reality for fixture design and assembly - Li, Qiang (2009)
Due to today's heavy, growing competition environment, manufacturing companies have to develop and employ new emerging technologies to increase productivity, reduce production costs, improve product quality, and shorten lead time. The domain of Virtual Reality (VR) has gained great attention during the past few years and is currently explored for practical uses in various industrial areas e.g. CAD, CAM, CAE, CIM, CAPP and computer simulation etc.